2015
DOI: 10.1016/j.molcel.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Independent Role of IKKα/IKKβ in Preventing RIPK1 Kinase-Dependent Apoptotic and Necroptotic Cell Death during TNF Signaling

Abstract: TNF is a master pro-inflammatory cytokine. Activation of TNFR1 by TNF can result in both RIPK1-independent apoptosis and RIPK1 kinase-dependent apoptosis or necroptosis. These cell death outcomes are regulated by two distinct checkpoints during TNFR1 signaling. TNF-mediated NF-κB-dependent induction of pro-survival or anti-apoptotic molecules is a well-known late checkpoint in the pathway, protecting cells from RIPK1-independent death. On the other hand, the molecular mechanism regulating the contribution of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
359
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(383 citation statements)
references
References 58 publications
23
359
0
1
Order By: Relevance
“…The kinase activity of RIPK1 has also been known to mediate TNFα-mediated apoptosis, termed RDA, when cells are deficient for TAK1, IKKs, or cIAP1/2 (Mihaly et al 2014;Dondelinger et al 2015). Spata2 −/− MEFs showed a partial resistance against RDA induced by the TNFα and TAK1 inhibitor (5Z)-7-oxozeaenol (5Z-7) compared with Spata2 + MEFs (Fig.…”
Section: Spata2 Regulates Apoptosismentioning
confidence: 99%
“…The kinase activity of RIPK1 has also been known to mediate TNFα-mediated apoptosis, termed RDA, when cells are deficient for TAK1, IKKs, or cIAP1/2 (Mihaly et al 2014;Dondelinger et al 2015). Spata2 −/− MEFs showed a partial resistance against RDA induced by the TNFα and TAK1 inhibitor (5Z)-7-oxozeaenol (5Z-7) compared with Spata2 + MEFs (Fig.…”
Section: Spata2 Regulates Apoptosismentioning
confidence: 99%
“…Therefore, mechanisms regulating RIPK1 kinase-dependent and -independent functions play a critical role in liver homeostasis and disease. Previous studies suggested that IκB kinases directly phosphorylate RIPK1 to regulate its prosurvival functions (23,45); however, it remains unclear whether NEMO regulates RIPK1 by facilitating its phosphorylation by IKKs.…”
Section: Discussionmentioning
confidence: 99%
“…induction remains an enigma, and necroptotic RIPK1 substrates have not yet been identified [3]. RIPK1 kinase activity also regulates apoptosis in certain conditions [35,[43][44][45], suggesting that the same RIPK1 substrate may control both necroptosis and apoptosis. It is tempting to speculate that RIPK1 itself is its main substrate and that RIPK1 autophosphorylation creates an open conformation allowing the interaction with pro-death molecules such as FADD (Fasassociated DD) and RIPK3.…”
Section: Ubiquitously Expressed Ripk1 Is a Master Regulator Of Cell Dmentioning
confidence: 99%
“…In addition, all three proteins are capable of inducing cell death downstream of these receptors [3,52,53]. In the case of RIPK1, cell death induction relies on its kinase activity [3,35,45]. However, IMD lacks the N-terminal kinase domain characteristic for Craniata RIPK1.…”
Section: Ripk1 Is Composed Of An N-terminal Kinase Domain Linked By Amentioning
confidence: 99%